INFORMATION ON THE WORK OF "SHIFA UL-ILAL" BY ALIKHANTURA SOGUNINY (Academicia Globe: Inderscience Research, 2023)
The medical treatise "Shifa ul-ilal" written by Alikhontora Soguni is the product of his experience accumulated during his thirty years of life. The reasons for writing "Shifa ul-ilal" are given as follows in the work "Sadness of Turkistan", which embodies the memories of this work: I wrote a book in the clear Turkish language and named it Shifa ul-ilal with the hope that it will be a memory for my generation."1 2. Commentaries on this treatise have been written by today's scholars.